THE EFFECTIVENESS OF PROBLEM-BASED LEARNING BASED ON SOCIO-SCIENTIFIC ISSUES ON STUDENTS' CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW - Fatimah, Siti; Rahayu, Yuni Sri; Raharjo, Raharjo (Universitas Labuhanbatu, 2025)
Purpose– This study aims to analyze the impact of learning using the Socio-Scientific Issues (SSI)-based Problem-Based Learning (PBL) model on students' critical thinking skills in biology. Although various studies have examined PBL and SSI separately, there has not yet been a comprehensive study that summarizes the combined effectiveness of the PBL-SSI model and maps the development of research in this field. This study fills this gap through a systematic analysis of the latest empirical findings.Methodology – This study employed the Systematic Literature Review (SLR) method, adhering to the PRISMA guidelines. The articles analyzed were 35 indexed articles published between 2019 and 2024 with the keywords 'Problem-Based Learning (PBL)', 'Socio-Scientific Issues (SSI)', and 'Critical Thinking'. VOSviewer was used to map related keywords, followed by qualitative analysis.Findings – The study's results indicate that approximately 80% of studies report a significant improvement in students' critical thinking skills following the application of the PBL-SSI model. Environmental topics such as pollution, climate change, and renewable energy are the most dominant themes due to their relevance and authenticity. Bibliometric analysis also confirms a strong correlation between the keywords